Molecular Biotechnology - Primrose, S B (Blackwell Scientific Publications, 1991)
Aims to examine all aspects of the exploitation of living organisms and their components. There is material on the application of molecular biology in medicine, the engineering of proteins and enzymes for commercial use, the implication of transgenic animals, and the monoclonal antibody.